Pygmy squids and giant brains: Mapping the complex cephalopod CNS by phalloidin staining of vibratome sections and whole-mount preparations - Wollesen, T.; Loesel, R.; Wanninger, A. (Journal of neuroscience methods, 2009)
Among bilaterian invertebrates, cephalopod molluscs (e.g., squids, cuttlefish and octopuses) have a central nervous system (CNS) that rivals in complexity that of the phylogenetically distant vertebrates (e.g., mouse and human). However, this prime example of convergent evolution has rarely been the subject of recent developmental and evolutionary studies, which may partly be due to the lack of suitable neural markers and the large size of cephalopod brains. Here, we demonstrate the usefulness of fluorescence-coupled phalloidin to characterize the CNS of cephalopods using histochemistry combined with confocal laser scanning microscopy. Whole-mount preparations of developmental stages as well as vibratome sections of embryonic and adult brains were analyzed and the benefits of this technique are illustrated. Compared to classical neuroanatomical and antibody-based studies, phalloidin labeling experiments are less time-consuming and allow a high throughput of samples. Besides other advantages summarized here, phalloidin reliably labels the entire neuropil of the CNS of all squids, cuttlefish and octopuses investigated. This facilitates high-resolution in toto reconstructions of the CNS and contributes to a better understanding of the organization of neural networks. Amenable for multi-labeling experiments employing antibodies against neurotransmitters, proteins and enzymes, phalloidin constitutes an excellent neuropil marker for the complex cephalopod CNS.